Paediatric condylar trauma – primary management considerations – A review - Abhay Taranath Kamath; Sreea Roy; Deepika Pai (Journal of Oral Biology and Craniofacial Research)
Children are not simply ‘‘small adults’’, and the application of adult-type treatment can be inappropriate in many circumstances. Their craniomaxillofacial (CMF) structure changes dramatically as children grow and develop. This anatomical change also changes the location, pattern, and nature of CMF injury. Similarly, condylar architecture and anatomy also differ in children, due to which the management of paediatric condylar fractures is strikingly different from adult condylar fractures. In addition to this physiological, and behavioural differences pose an additional challenge to a surgeon.Paediatric condylar fracture also considers conservative/non-operative treatment as an effective treatment option. However, the decision between operative and non-operative management compromises paediatric facial growth, precise reduction, and rigid fixation. This decision is crucial and is guided by many factors. Improper treatment protocol can have a devastating effect on a child facial growth and development. It can lead to various deforming complications mainly ankylosis. Hence treatment of paediatric condylar fracture should be well planned and executed.